Effect of Benson relaxation response technique on the quality of life among patients with systemic lupus erythematous: quasi-experimental study - Rami Masa'Deh; Arwa Masadeh; Basema Mohammad Nofal (Lupus Science and Medicine)
Objectives To investigate the effect of Benson relaxation response technique (BRRT) on the quality of life (QOL) among patients with systemic lupus erythematous (SLE).Methodology A quasi-experimental design was used to conveniently recruit 170 patients with SLE. Participants were divided into two groups, the control and the intervention group for which the BRRT intervention was administered. Utilising an online questionnaire, the QOL was assessed among the two groups, before and 2 months after the intervention, using the Arabic version of the short form 36-item health survey.Results After 2 months of the intervention, the intervention group exhibited significantly higher levels in both components of QOL; physical (t(143.31)=15.35, p<0.001); and mental component (t(143.58)=12.35, p<0.001). Additionally, for the intervention group, the results revealed a statistically significant increase in the levels of both components from baseline measurement; physical (t(84)=−16.24, p<0.001) and mental component (t(84)=−12.93, p<0.001).Conclusion The findings demonstrate a notable positive impact of BRRT on QOL among patients with SLE. Healthcare professionals can potentially improve the overall well-being of patients with SLE and complement traditional treatment by implementing BRRT into their care.